A Bioassay Method for Metabolizable Energy of Feedstuffs for Peking Ducks - Niu, Zhuye; Zhang, Chunlei; Liu, Fuzhu (International Journal of Poultry Science, 2008)
Three experiments were carried out to determine optimal feed input and excreta collection time in bioassay of feedstuff true metabolizable energy for ducks. In experiment 1, 20 drakes had been food withdrawn and were allocated to 4 groups, each of which contained 5 birds. Birds of each group were force-fed 50 g complete feed, approximately 48 h after food withdrawal. The excreta voided during the exact 56 h following feeding were collected. In experiment 2, 28 drakes were force-fed 50 g complete feed, approximately 48 h after food withdrawal. 4 birds were killed by an intravenous dose of sodium pentobarbitone 4 h, 8 h, 14 h, 24 h, 32 h, 38 h and 48 h after feeding. The residues in alimentary canal were collected and dried in an oven at 65 °C. In experiment 3, 70 mature drakes were allocated to 7 groups. The treatments comprised an unfed negative control and five levels of feed input ( 30, 50, 70, 90, 110 and 150 g complete feed). The birds were force-fed at approximately 48 h after food withdrawal. The excreta voided during the exact 36 h following feeding were collected. The results indicated that the time prior to force-feeding and excreta collection period should be 32-36 h when evaluating feed metabolizable energy and 50-70 g feed per bird is feasible for evaluating feed metabolizable energy.